Two Distinct Superoxidase Dismutases (SOD) Secreted by the Helminth Parasite Fasciola hepatica Play Roles in Defence against Metabolic and Host Immune Cell-Derived Reactive Oxygen Species (ROS) during Growth and Development - Nichola Eliza Davies Calvani; Carolina De Marco Verissimo; Heather Louise Jewhurst; Krystyna Cwiklinski; Andrew Flaus; John Pius Dalton (Antioxidants, 2022)
The antioxidant superoxide dismutase (SOD) catalyses the dismutation of superoxide, a dangerous oxygen free radical, into hydrogen peroxide and molecular oxygen. Superoxide generation during the oxidative burst of the innate immune system is considered a key component of the host defence against invading pathogens. We demonstrate the presence and differential expression of two SODs in Fasciola hepatica, a leaderless cytosolic (FhSOD1) and an extracellular (FhSOD3) form containing a secretory signal peptide, suggesting that the parasites exploit these enzymes in distinct ways to counteract reactive oxygen species (ROS) produced by cellular metabolism and immune defences. Both enzymes are highly expressed by the infective newly excysted juvenile (NEJ) stages and are found in abundance in their excretory–secretory products (ES), but only FhSOD1 is present in adult ES, suggesting that the antioxidants have different functions and pathways of secretion, and are under separate temporal expression control during the migration, growth, and development of the parasite. Functionally, the recombinant FhSOD1 and FhSOD3 exhibit similar activity against superoxide to their mammalian counterparts. Confocal immuno-localisation studies demonstrated the presence of FhSOD1 and FhSOD3 on the NEJ tegument and parenchyma, supporting our suggestion that these enzymes are secreted during host invasion to protect the parasites from the harmful oxidative bursts produced by the activated innate immune response. By producing superoxide enzymatically in vitro, we were able to demonstrate robust killing of F. hepatica NEJ within 24 h post-excystment, and that the lethal effect of ROS was nullified with the addition of SOD and catalase (the antioxidant enzyme responsible for the dismutation of hydrogen peroxide, a by-product of the SOD reaction). This study further elucidates the mechanism by which F. hepatica protects against ROS derived from cellular metabolism and how the parasite could mitigate damage caused by the host’s immune response to benefit its survival.